Hierarchy of Branding of Abandoned Animal Protection Organizations: The Case of Animal Defender Indonesia - Livo Februsa; Mulyadi (Jobmark: Journal of Branding and Marketing Communication, 2022)
This paper explores the branding strategies of Animal Defenders Indonesia (ADI), an organization dedicated to rescuing and protecting neglected animals. With a focus on the AKIELS model—spanning Brand Awareness to Brand Spirituality—the study evaluates ADI's positioning in animal protection. Beginning with an overview of the prevalence of pet neglect, the paper introduces ADI as a critical player founded in 2011 to address the challenges faced by abandoned and injured animals in Indonesia. ADI's multifaceted approach, encompassing Rescue, Rehab, Rehome, and Education, forms the foundation of its mission to save and protect animals, particularly those subjected to abandonment, injury, or abuse. The organization also emphasizes public awareness through educational initiatives. The paper then delves into the AKIELS framework, analyzing ADI's branding strategies across various platforms. Drawing on previous research, the study highlights the role of social media in ADI's communication strategies, notably successful campaigns like "Adopt Don't Shop." Methodologically, a qualitative approach employing positive content analysis focuses on ADI's documents, publications, and related materials. The findings reveal robust Brand Awareness, especially on YouTube and Instagram, but recommend enhanced visibility through diversified content and strategic event marketing. While robust Brand Knowledge is evident on YouTube and Instagram, attention is needed for Facebook engagement and broader media coverage. The positive Brand Image built by ADI requires improvements in specific areas, such as Google search visibility and strategic event promotion. The paper concludes by emphasizing ADI's strong foundation, proposing strategies for improved content, community interaction, and marketing events to strengthen its brand presence and relationships with the audience.